Overflowing tables: Changes in the energy intake and the social context of Thanksgiving in the United States. Issue 1 (2nd January 2022) - Thomas, Diana; Yoshitani, Gail; Turner, Dusty; Hariharan, Ajay; Bhutani, Surabhi; Allison, David B; Moniz, Amanda; Heymsfield, Steven; Schoeller, Dale A; Hull, Holly; Fields, David
Abstract: In the United States, recent studies have demonstrated weight gain over Thanksgiving contributing to a significant portion of annual national weight gain. Understanding the social context of how Thanksgiving celebrations were perceived is critical for preventing and reducing excess weight during this time. Energy intake from present-day data was back-calculated from body weight data collected in participants before and after Thanksgiving. Similar calculations were performed in studies that also included Christmas. A Latent Dirichlet Allocation analysis of topics scraped from Twitter under the hashtag #thanksgiving was performed. The top topics and search queries from Google Trends on Thanksgiving 2020 were also identified. Since 1621, the social context of Thanksgiving has evolved from a focus on prayer and celebrated gratitude to a focus on food, football, and retail. What is served on Thanksgiving and its energy content has not substantially changed since the late 18th century. On the other hand, body weights and mean energy intake have steadily increased over time with the most rapid increases occurring since 1941. The shift in the social context of Thanksgiving and other factors of an existing obesogenic environment have likely combined to generate increased energy intake and weight gain during Thanksgiving.